An innovative SMS intervention to improve adherence to stimulants in children with ADHD: Preliminary findings. (August 2020) - Fried, Ronna; DiSalvo, Maura; Kelberman, Caroline; Adler, Amos; McCafferty, Debra; Woodworth, K Yvonne; Green, Allison; Biederman, Itai; Faraone, Stephen V; Biederman, Joseph
Background: Although large datasets document that stimulants decrease the risk for many adverse ADHD-associated outcomes, compliance with stimulants remains poor. Aims: This study examined the effectiveness of a novel ADHD-centric text messaging-based intervention aimed to improve adherence to stimulant medications in children with ADHD. Methods: Subjects were 87 children aged 6–12, who were prescribed a stimulant medication for ADHD treatment. Prescribers gave permission to contact their patients for participation in the study. Subjects were primarily from the primary care setting with a subsample of psychiatrically referred subjects for comparison. Age- and sex-matched comparators were identified (3:1) from the same pool of prescriber-approved subjects that did not participate. Timely prescription refills (within 37 days) were determined from prescription dates documented in patients' electronic medical record. Results: Eighty-five percent of SMS intervention patients refilled their prescriptions in a timely manner compared with 62% of patients receiving treatment as usual (OR = 3.46, 95% CI: 1.82, 6.58; p  < 0.001). The number needed to treat statistic was computed as five, meaning for every five patients who receive the SMS intervention, we can keep one adherent to their stimulant treatment. Conclusions: These preliminary findings support the potential utility of a readily accessible technology to improve the poor rate of adherence to stimulant treatment in children with ADHD. To the best of our knowledge, this study is the first digital health intervention aimed at improving adherence to stimulant medication for children with ADHD. These results support the need for further examination of this technology through more definitive randomized clinical trials.